Medicaid Expansion and the Mental Health of Spousal Caregivers - Joan Costa-i-Font; Nilesh Raut; Courtney Harold Van Houtven (Center for Economic Studies and ifo Institute (CESifo), 2021)
Health insurance expansions can exert wellbeing effects on individuals who provide informal care to their loved ones, reducing their experience of depression. This study exploits evidence from the Affordable Care Act's (ACA) Medicaid expansion to examine the effects on the mental wellbeing of informal caregivers. Drawing on an event study and a Difference-in-Differences (DID) design we investigate the policy impact of ACA Medicaid expansion using longitudinal evidence (from the Health and Retirement Study, HRS) for 2010 to 2018 for low-income individuals aged 64 or below. We find that ACA's Medicaid expansion reduced depressive symptoms among caregivers, and specifically we estimate that exposure to ACA Medicaid expansion gives rise to a 0.38 points (equivalent to 4-5%) reduction in the CESD score (a negative scale in which the lowest scale indicates the best mental wellbeing). We also find that ACA Medicaid causes a spillover effect at the household level, improving the well-being of the spouse care recipient. Our results are robust to various specifications, and we identify several potential driving mechanisms for the findings: reductions in out of -pocket expenses and labor supply and, as expected, increased Medicaid uptake. The evidence from falsification tests confirms that the estimated effects are purely due to ACA's Medicaid expansion and no other phenomena.
Keywords: I18; 330; insurance expansion; Medicaid; mental wellbeing; ACA; spousal mental health; informal care